2006
DOI: 10.1590/s0103-97332006000700017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenic impurity in ridge quantum wire

Abstract: The binding energies as well as wave functions of hydrogenic impurities located in V-groove GaAs/Al x Ga 1−x As quantum wires are calculated for different positions of the impurity inside the wires. The variational method is used and the carrier ground states are analytically calculated by an effective potential scheme together with a suitable coordinate transformation that allows the decoupling of the two-dimensional Schrodinger equation. The results are in good agreement with experimental points and other pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Here, y 1 ( x ) and y 2 ( x ) describe the upper and bottom boundaries of V‐groove quantum wire (see Fig. 1) 29–32. In the last decade, considerable experimental and theoretical attention was devoted to V‐shaped quantum wires.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, y 1 ( x ) and y 2 ( x ) describe the upper and bottom boundaries of V‐groove quantum wire (see Fig. 1) 29–32. In the last decade, considerable experimental and theoretical attention was devoted to V‐shaped quantum wires.…”
Section: Theorymentioning
confidence: 99%
“…We use the density matrix formulation to obtain the linear and third‐order nonlinear changes in refractive index and the absorption coefficient. To attain our purpose, we apply the analytical solutions of Schrödinger equation obtained in the previous work 29, 30 for a V‐groove quantum wire.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the properties of impurity states in V-groove systems have also been investigated. [22][23][24][25][26]. Experimental results related with the luminescence of the single and VGQWR superlattices were reported by Maciel et al and by Khordad et al.…”
mentioning
confidence: 81%
“…On the other hand, the properties of impurity states in V‐groove systems have also been investigated. . Experimental results related with the luminescence of the single and VGQWR superlattices were reported by Maciel et al and by Khordad et al , whereas nonlinear absorption coefficient and refractive index changes were theoretically obtained by Khordad et al .…”
Section: Introductionmentioning
confidence: 89%
“…1 Binding energies of a hydrogenic donor in different quantum wells with GaAs/Ga 1-x Al x As have been investigated experimentally and theoretically by many authors. [2][3][4][5][6][7] Several authors have reported the effect of perturbations on hydrogenic donor binding energy in different quantum wells. 8,9 Surface Quantum Well (SQW) composed of vacuum/GaAs/GaAlAs are of considerable interest due to: (1) the presence of localised states even above the single quantum barrier in the GaAlAs layer; 10 and (2) the image charges that arise from the large dielectric mismatch at the single vacuum/GaAs interface.…”
Section: Introductionmentioning
confidence: 99%